Patient-reported outcome tools of acupuncture clinical trials in mainland China: a cross-sectional study - Cao, Feng; Dong, Yue; Li, Zhi-Qiang; Wang, Xue-Feng; Su, Cheng-Yuan; Lv, Jia-Xuan; Shi, Zhong-Yu; Du, Ming-Hong; Zhang, Xin-Yue; Rong, Hong-Guo; Fei, Yu-Tong (Frontiers in Neurology, 2025)
Background and objectiveNowadays, the number of acupuncture clinical trials is dramatically increasing. In acupuncture clinical research, patient-reported outcome measurements are important evaluation tools, but there is a lack of systematic survey. This study aims to evaluate the characteristics and application of PRO measurements in acupuncture clinical trials in mainland China, further exploring and developing patient-reported outcomes (PROs) that are in line with the characteristics of acupuncture treatment.MethodsThis cross-sectional study analyzed acupuncture clinical trials in mainland China (2010–2022). Data were extracted from ClinicalTrials.gov and the Chinese Clinical Trial Registry. Acupuncture interventional clinical trials conducted or recruited in mainland China were included. For each included trial, data were extracted on aspects including the clinical trial phase, study setting, participant age, disease, and PRO measurements. Descriptive statistics were performed using Stata 14.0 (StataCorp). Microsoft Excel 2020 (Microsoft Corporation, Redmond, WA, United States) and python3.9 (Netherlands) were used to analyze and display the PROs data.ResultsOut of a total of 962 trials, 193 trials listed PROs as primary outcomes, 208 trials listed PROs as secondary outcomes, and 342 trials listed PROs as co-primary outcomes. Musculoskeletal symptoms (13.5%), neurological disorders (11.7%), and mental health conditions (9.6%) were the most common conditions assessed by PRO tools. The Visual Analogue Scale (VAS) was the most frequently used measurement (30%), followed by concepts related to health-related quality of life (HRQOL). The Pittsburgh Sleep Quality Index (PSQI), 36-Item Short Form Survey (SF-36), and Self-Rating Depression Scale (SDS) were the most common PRO tools utilized in these trials. Clinical trials incorporating PROs were predominantly conducted in the eastern, northern, and southwestern regions of mainland China. Only a part of acupuncture clinical trials (15.2%) used placebos and reported PRO.Conclusions and relevanceIn this cross-sectional study, the use of PROs has increased over the past few decades based on acupuncture clinical trials conducted in mainland China. Given the uneven distribution and lack of acupuncture-specific PROs in the application of acupuncture clinical trials, further attention should be paid to the standardization and regulation of acupuncture-specific scales in the field of acupuncture clinical research.